2014
DOI: 10.1016/j.ijrobp.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fast Helical 4D-CT Acquisition Technique to Generate Low-Noise Sorting Artifact–Free Images at User-Selected Breathing Phases

Abstract: Purpose To develop a novel 4-dimensional computed tomography (4D-CT) technique that exploits standard fast helical acquisition, a simultaneous breathing surrogate measurement, deformable image registration, and a breathing motion model to remove sorting artifacts. Methods and Materials Ten patients were imaged under free-breathing conditions 25 successive times in alternating directions with a 64-slice CT scanner using a low-dose fast helical protocol. An abdominal bellows was used as a breathing surrogate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 34 publications
(38 reference statements)
3
80
0
Order By: Relevance
“…An initial clinical study of the 5DCT technique, described by Thomas et al, 7 achieved a mean model error of 1.19 ±0.37 mm across ten patients. The quantity reported as model error by Thomas et al 7 is referred to as model residual in this study because similarity between the original scans and corresponding 5DCT reconstructions was subsequently adopted as the primary error metric.…”
Section: Discussionmentioning
confidence: 99%
“…An initial clinical study of the 5DCT technique, described by Thomas et al, 7 achieved a mean model error of 1.19 ±0.37 mm across ten patients. The quantity reported as model error by Thomas et al 7 is referred to as model residual in this study because similarity between the original scans and corresponding 5DCT reconstructions was subsequently adopted as the primary error metric.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques have been proposed for retrospective sorting-based approaches with the aim of reducing motion artifacts in 4DCT images [15, 17-23]. Of these, respiratory motion model based techniques have shown promising improvement in mitigating sorting artifacts [18, 19, 24, 25], besides the additional attractive qualities of their predictive power. In particular, Thomas et al [25] demonstrated the generation of motion artifact-free 4DCT images at user-selected breathing phases based on a fast helical CT acquisition technique and a deformable lung motion model.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, respiratory motion model based techniques have shown promising improvement in mitigating sorting artifacts [18, 19, 24, 25], besides the additional attractive qualities of their predictive power. In particular, Thomas et al [25] demonstrated the generation of motion artifact-free 4DCT images at user-selected breathing phases based on a fast helical CT acquisition technique and a deformable lung motion model. The model was based on Low et al [26], employing two surrogates, breathing amplitude and rate, as independent variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] Various techniques have been proposed for retrospective sorting-based approaches with the aim of reducing irregular breathing artifacts in 4DCT images. [17][18][19][20][21] In particular, Thomas et al demonstrated the acquisition of sorting-artifact-free CT images at arbitrary user-selected breathing phases based on a lung motion model 21 first published by Low et al 22 This approach is termed 5DCT (three spatial dimensions along with the breathing amplitude and breathing rate). The 5DCT image acquisition aims at capturing the extent of lung tissue motion by performing multiple high-pitch (1.2) helical scans with a simultaneously recorded surrogate signal.…”
Section: Introductionmentioning
confidence: 99%